2010
DOI: 10.1007/s11357-010-9192-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme (ACE) genotypes and disability in hospitalized older patients

Abstract: The association between angiotensinconverting enzyme (ACE) genotypes and functional decline in older adults remains controversial. To assess if ACE gene variations influences functional abilities at older age, the present study explored the association between the common ACE insertion/ deletion (I/D) polymorphism and disability measured with activities of daily living (ADL) in hospitalized older patients. We analyzed the frequency of the ACE genotypes (I/I, I/D, and D/D) in a population of 2,128 hospitalized o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
2
9
0
1
Order By: Relevance
“…Few studies investigated the genetic variations influencing physical abilities at old age and samples were mainly drawn from hospitalized and affected patients. Positive association was reported between ADL levels and ACE gene by Seripa et al (2011), while no correlation was found with APOE gene by Kulminski et al (2008) and Bader et al (1998), the last in a cohort of 253 healthy and disabled Italian octo- and nonagenarians. As for cognitive functioning, studies found an involvement of genes specifically involved in neurological metabolism and dopaminergic neuromodulation, as APOE, COMT, BDNF and DTNBP1 genes, with cognitive ability in older adults less than 85 years (De Blasi et al, 2009; Lindenberger et al, 2008).…”
Section: Discussionmentioning
confidence: 90%
“…Few studies investigated the genetic variations influencing physical abilities at old age and samples were mainly drawn from hospitalized and affected patients. Positive association was reported between ADL levels and ACE gene by Seripa et al (2011), while no correlation was found with APOE gene by Kulminski et al (2008) and Bader et al (1998), the last in a cohort of 253 healthy and disabled Italian octo- and nonagenarians. As for cognitive functioning, studies found an involvement of genes specifically involved in neurological metabolism and dopaminergic neuromodulation, as APOE, COMT, BDNF and DTNBP1 genes, with cognitive ability in older adults less than 85 years (De Blasi et al, 2009; Lindenberger et al, 2008).…”
Section: Discussionmentioning
confidence: 90%
“…These effects appear to be unique to ACE-Is, when compared to other classes of anti-hypertensives [75], further supporting that the benefits are independent of the drugs BP lowering properties. In addition, individuals with polymorphisms, resulting in low ACE activity, have an enhanced response to training [76] although this contrasts with the observations of increased ADL disability for the same gene variants in older populations [49]. The association between treatment with either ACE-Is and/or ARBs, with a lower incidence of falls also supports the theory that these medications may produce global effects on physical function [47].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the discontinuation of ACE-Is in those with AD is associated with increased rates of functional decline [48]. Studies investigating ACE genotypes in functional decline suggest both increased [49] and decreased disability [50]. There is also evidence that ACE-Is modulate mood, including anxiety [51] and depression in hypertensive patients with normal cognition [52].…”
Section: Effects Of Cace-is On Adls and The Behavioral And Psychologimentioning
confidence: 99%
“…Only one of these four ACE studies reported significant genotypic relationship to performance at baseline, with the ACE insertion/deletion (ACE ID) group having a significantly greater baseline handgrip strength (Bustamante-Ara et al 2010). In support of a possible genetic link to baseline function, Seripa et al (2011) demonstrated that the ACE II genotype was associated with increased risk of limitations in activities of daily living in hospitalised older patients. Of the two studies that assessed training-related changes in older adults, both reported significantly greater improvements in strength and power measures for those with the ACE D allele (Giaccaglia et al 2008;Pereira et al 2013).…”
Section: Reviewing Manuscriptmentioning
confidence: 96%
“…When expressed, the ACE gene produces angiotensin-converting enzyme protein. This ACE protein plays a key role in regulating the activity of the rennin-angiotensin system, thereby directly influencing blood pressure and fluid balance and indirectly influencing cardiovascular and musculoskeletal structure and function (Puthucheary et al 2011;Seripa et al 2011). Indeed, a functional polymorphism in the human ACE gene, the intron 16 insertion (I) allele, has been associated with an enhanced cardiovascular response to training (Myerson et al 1999), while the deletion (D) allele has been associated with a superior muscle size and strength response to training (Puthucheary et al 2011;Woods et al 2001).…”
Section: Introductionmentioning
confidence: 99%